Clinical efficacy of angiotensin receptor-neprilysin inhibitor in de novo heart failure with reduced ejection fraction - Su Yeong Park; Min Gyu Kong; Inki Moon; Hyun Woo Park; Hyung-Oh Choi; Hye Sun Seo; Yoon Haeng Cho; Nae-Hee Lee; Kwan Yong Lee; Ho-Jun Jang; Je Sang Kim; Ik Jun Choi; et al. (The Korean Journal of Internal Medicine, 2023)
Background/Aims We aimed to analyze the efficacy of angiotensin receptor-neprilysin inhibitor (ARNI) by the disease course of heart failure (HF). Methods We evaluated 227 patients with HF in a multi-center retrospective cohort that included those with left ventricular ejection fraction (LVEF) ≤ 40% undergoing ARNI treatment. The patients were divided into patients with newly diagnosed HF with ARNI treatment initiated within 6 months of diagnosis (de novo HF group) and those who were diagnosed or admitted for HF exacerbation for more than 6 months prior to initiation of ARNI treatment (prior HF group). The primary outcome was a composite of cardiovascular death and worsening HF, including hospitalization or an emergency visit for HF aggravation within 12 months. Results No significant differences in baseline characteristics were reported between the de novo and prior HF groups. The prior HF group was significantly associated with a higher primary outcome (23.9 vs. 9.4%) than the de novo HF group (adjusted hazard ratio 2.52, 95% confidence interval 1.06–5.96, p = 0.036), although on a higher initial dose. The de novo HF group showed better LVEF improvement after 1 year (12.0% vs 7.4%, p = 0.010). Further, the discontinuation rate of diuretics after 1 year was numerically higher in the de novo group than the prior HF group (34.4 vs 18.5%, p = 0.064). Conclusions The de novo HF group had a lower risk of the primary composite outcome than the prior HF group in patients with reduced ejection fraction who were treated with ARNI.